Escritoras abolicionistas no Brasil-Império: Maria Firmina dos Reis e Júlia Lopes de Almeida na luta contra a escravidão - Zin, Rafael Balseiro (2022)
The present work aims to carry out a comparative study of the abolitionist texts of the writers Maria Firmina dos Reis (1822-1917) and Júlia Lopes de Almeida (1862-1934), who were active in the fight against slavery during the final years of the Empire of Brazil, from an analysis of literary fragments extracted from their main works focused on this theme: the novels Úrsula, from 1859, and A família Medeiros, written between 1886 and 1888, but only published in 1891. Beginning from an interdisciplinary perspective, which establishes a dialogue between literary studies and studies of Brazilian social thought, the main objective of the research is to recover the political thought of these authors, seeking to arrive at the meanings they attributed to the antislavery cause in vogue at that time. At the same time, the intention of this work is to understand how the participation of women writers in the process of abolition of slavery in Brazil took place, bearing out the fact that they had made their own literature an instrument of combat, with a view to disseminating among the reading public their ideals of freedom, justice and equality, whether in the relationship between men and women, or in the relationship between masters and slaves